Prevalence and factors affecting nocturnal enuresis among primary school children in Baddi, Himachal Pradesh, India - Bansal, Naveen; Goyal, Manju Bala (International Journal of Contemporary Pediatrics, 2020)
Background: Enuresis is defined as involuntary urination beyond the age of 5 years. The present study was done to determine the prevalence of nocturnal enuresis and its associated risk factors in children in Baddi, Himachal Pradesh. Methods: This was a prospective observational cross-sectional study done in children in the age group of 5-11 years over a period of 18 months. Nocturnal enuresis was defined using the DSM IV criteria. Data analysis was done using chi square test. Results: The total sample size was 2144 and the prevalence of nocturnal enuresis was found to be 22.0% (n=472). There was statistically significant relationships between nocturnal enuresis and history of nocturnal enuresis in siblings (p=0.0018), history of deep sleep (p<0.05), history of perianal itching (p<0.05), history of urinary tract infection (p<0.05), poor academic performance (p<0.05). Conclusions: Nocturnal enuresis is a result of complex interplay of multiple physiological and psychological factors. Parents need to be sensitised and educated regarding these causation factors for better prevention and treatment of nocturnal enuresis.